(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Medical ethics is important for every medical practitioner. A doctor should acquire sound knowledge on medical ethics which is very much important in clinical practice. Medical ethics is a system of moral principles that apply values and judgments to the practice of medicine. Medical ethics derive from numerous sources. Physicians face ethical dilemmas more frequently as community relies on physicians for critical services. Ethics are a useful element for solving these dilemmas. Medical ethics based on four basic principles: autonomy, beneficence, nonmaleficence and justice. Physicians are expected to have higher standards than the law. The code of medical ethics provides a guide line in the context of doctor patient relationship and the society. JCMCTA 2016 ; 27 (2) : 9 - 11